Characterising GPCR–ligand interactions using a fragment molecular orbital-based approach. (April 2019) - Heifetz, Alexander; James, Tim; Southey, Michelle; Morao, Inaki; Aldeghi, Matteo; Sarrat, Laurie; Fedorov, Dmitri G; Bodkin, Mike J; Townsend-Nicholson, Andrea
Graphical abstract: Abstract : There has been fantastic progress in solving GPCR crystal structures. However, the ability of X-ray crystallography to guide the drug discovery process for GPCR targets is limited by the availability of accurate tools to explore receptor–ligand interactions. Visual inspection and molecular mechanics approaches cannot explain the full complexity of molecular interactions. Quantum mechanical approaches (QM) are often too computationally expensive, but the fragment molecular orbital (FMO) method offers an excellent solution that combines accuracy, speed and the ability to reveal key interactions that would otherwise be hard to detect. Integration of GPCR crystallography or homology modelling with FMO reveals atomistic details of the individual contributions of each residue and water molecule towards ligand binding, including an analysis of their chemical nature.